2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5626264
|View full text |Cite
|
Sign up to set email alerts
|

Skin relaxation predicts neural firing rate adaptation in SAI touch receptors

Abstract: In response to ramp-and-hold indentation, the slowly-adapting type I (SAI) afferent exhibits an exponential decrease in its firing frequency during the hold phase. Such adaptation may be tied to skin relaxation but is neither well understood nor has it been quantitatively modeled. The specific hypothesis of this work is that skin relaxation is a primary contributor to observed changes in firing rate. Double exponential functions were fit to 21 responses from a mouse SAI afferent for both instantaneous firing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…As the magnitude of indentation increased from 1.2 mm (indentation type III ), 1.3 mm ( IV ), to 1.4 mm ( V ) the spiking-sensor model predicted a trend of increased spike firing, evident from decreasing average ISI s (98.81, 54.51, 41.11 ms respectively) within the static hold phase (Figure 8b). These predictions fit favorably (mean stat_FSS  = 0.925) to those observed average static ISI s (93.31, 36.28, 29.89 ms respectively) and agree with works by Mountcastle et al [33] and Ge and Khalsa [29]. Mountcastle et al [33] demonstrated a roughly positive and linear relationship between stimulus displacement magnitude and firing rate reported by SAI afferents in the macaque monkey.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As the magnitude of indentation increased from 1.2 mm (indentation type III ), 1.3 mm ( IV ), to 1.4 mm ( V ) the spiking-sensor model predicted a trend of increased spike firing, evident from decreasing average ISI s (98.81, 54.51, 41.11 ms respectively) within the static hold phase (Figure 8b). These predictions fit favorably (mean stat_FSS  = 0.925) to those observed average static ISI s (93.31, 36.28, 29.89 ms respectively) and agree with works by Mountcastle et al [33] and Ge and Khalsa [29]. Mountcastle et al [33] demonstrated a roughly positive and linear relationship between stimulus displacement magnitude and firing rate reported by SAI afferents in the macaque monkey.…”
Section: Discussionsupporting
confidence: 88%
“…The cylindrical tip’s dimensions were 14 mm height by 20 mm diameter. The use of this particular tip size and shape ensured that an equal state of normal stress was applied over the entire sensing area surface of the embedded sensor and minimized the out-of-plane shear stress [29]. These conditions thereby matched those for the mouse SAI afferent.…”
Section: Methodsmentioning
confidence: 99%
“…We therefore hypothesized that sensitivity to both M 0 and M0 arose from tissue viscoelasticity (cf. (Fraser et al, 2006; Williams et al., 2010)).…”
Section: Resultsmentioning
confidence: 99%
“…The excellent fit between data and model suggests that filtering of contact stresses by tissue viscoelasticity underlies spike rate adaptation, and thus plays a central role in determining the activity of Merkel and SA afferents (Williams et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…As interstitial fluid plays an important role in skin's viscoelasticity, the change of its amount and how the fluid is distributed within the tissue causes different relaxation behaviors. The increase of instantaneous modulus observed as the rate of loading increases may tend to agree, as well, with electrophysiological recordings from tactile mechanoreceptors where increased probe velocity yields higher firing rates from slowly adapting type I afferents [31], [32], though the neuron itself may play a role apart from the skin's response. This result may suggest a need to control loading velocity in electrophysiological experiments.…”
Section: Discussionmentioning
confidence: 73%